2001
DOI: 10.1111/1467-9396.00308
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Portfolio Equity Investments, Financial Liberalization, and Economic Development

Abstract: Reform of local capital markets and relaxation of capital controls to attract foreign portfolio investments (FPIs) has become an integral part of development strategy. The proximity of market openings and large, sudden shifts in international capital flows gave credence to the notion that the liberalization was the primary culprit in precipitating the recent Asian crisis. Hence, this paper reassesses the benefits and costs of FPIs from the perspective of the recipients. Specifically, it discusses the various F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 54 publications
(32 reference statements)
5
68
1
7
Order By: Relevance
“…Apart from unsustainable policies of the recipient countries, foreign portfolio investors were one of the main causes of this crisis. Domestic and international crisis can also interrupt the capital flows to a country; it occurred in Turkey when FPI inflows were strongly affected by the crisis of 2000 and FDI was strongly hit by the crisis of 2005-06 (Errunza, 2001;Goldstein & Razin, 2002;Durham, 2003;Lajuni, Ooi, & Ghazali, 2008;Uctum & Uctum, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from unsustainable policies of the recipient countries, foreign portfolio investors were one of the main causes of this crisis. Domestic and international crisis can also interrupt the capital flows to a country; it occurred in Turkey when FPI inflows were strongly affected by the crisis of 2000 and FDI was strongly hit by the crisis of 2005-06 (Errunza, 2001;Goldstein & Razin, 2002;Durham, 2003;Lajuni, Ooi, & Ghazali, 2008;Uctum & Uctum, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transmission mechanism between FPI and GDP has been summarized in the previous studies, e.g. Errunza and Losq (1985), Obstfeld (1994), Errunza et al (1998), Levine and Livine (2000), Errunza (2001), Perotti and Van (2001), Abdalla and Dafaalla (2011) and Todea and Pleşoianu (2013). FPI can influence domestic growth through its contribution in developing the local financial markets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Kim and Singal (2000) consider the level and volatility of returns in Jordan and Turkey around the opening up of their financial markets. Errunza (2001) focuses on issues pertaining to the liberalization and integration of financial markets in Egypt, Israel, Jordan, Morocco, and Turkey, but not the Persian Gulf region. Gulen and Mayhew (2000) include Israel in their study of stock market volatility before and after the introduction of equity-index futures trading in twenty-five countries.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant literatures have recognised the importance of FDI such as; (i) to provide a long-term capital which is normally missing in the target country yet suitable for economic development, (ii) to bring new technologies that are usually not available in the target country and expected to create spill-over (and subsequently crowding-in) effects as the new technologies usually spread beyond the foreign corporations, and (iii) to improve the business environment of the target country by introducing ethical business or rules of conduct. Errunza (2001) could be among the first to study the impact of FPI on economic development and concluded that resource mobilisation, contagion and volatility are unwarranted provided some preconditions for capital market openings and liberalisation sequencing are fully abide. The impact of AID could be a bit controversial as it requires us to distinguish between the effects of different kinds of aid, or else, the standard aid-growth regression may lead to erroneous conclusions due to this strategic bias problem (Minoiu & Reddy, 2009).…”
Section: Introductionmentioning
confidence: 99%